ANTHROPOLOGICAL ANOMALIES AS A SOURCE OF CORRUPTION - Isomiddinov Yunusjon Yusubboevich (Galaxy International Interdisciplinary Research Journal, 2023)
It is shown that there is an important "tie-in" of moral and legal aspects of corruption, which can be investigated more effectively from the psychological point of view. This is substantiated by the thesis of S. L. Rubinstein, a prominent domestic psychologist, that man is a big topic of world outlook, and above all of ethical order.